Impact of Multimodal Therapy on Margin Status on Overall Survival for Patients Undergoing Adrenalectomy for Localized Adrenocortical Carcinoma - Rashid Ali, Muhammad Asif, Haleemullah, Abdul Basit Niazi, Hira Anis Bumbia, Muhammad Ammar (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Adrenocortical carcinoma (ACC) is a rare and aggressive malignancy that arises from the adrenal cortex. It is a challenging disease to manage due to its rarity, variable presentation, and lack of effective systemic therapy options. Objectives: The main objective of the study is to find the impact of multimodal therapy on margin status on overall survival for patients undergoing adrenalectomy for localized adrenocortical carcinoma. Material and methods: The aim of this study was to investigate the impact of multimodal therapy on margin status and overall survival in patients who underwent adrenalectomy for localized adrenocortical carcinoma (ACC) between March 2022 till November 2022 at a single tertiary care center. Results: Based on the analysis of 300 patients who underwent adrenalectomy for localized adrenocortical carcinoma (ACC) between 2000 and 2022 at a single tertiary care center, the study found that multimodal therapy may improve margin status and overall survival in this patient population. Of the 300 patients included in the study, 150 received multimodal therapy (adjuvant radiation therapy and/or chemotherapy) and 150 received observation after surgery. The median follow-up time was 48 months. Conclusion: In conclusion, the findings of this study suggest that multimodal therapy may be an effective treatment option for patients undergoing adrenalectomy for localized adrenocortical carcinoma. Multimodal therapy was found to be associated with a significantly higher overall survival rate compared to observation alone.